Assessment of Acoustic Emission localization accuracy on damaged and healed concrete. (30th December 2016) - Tsangouri, Eleni; Karaiskos, Grigorios; Deraemaeker, Arnaud; Van Hemelrijck, Danny; Aggelis, Dimitrios
Highlights: The ultrasound source localization error is measured using Acoustic Emission as damage occurs in concrete. The localization error decreases after the autonomous healing of concrete. The integrated monitoring method will be applied on the healing concrete of the future. Abstract: The accuracy of ultrasound source localization is measured on damaged and autonomously healed concrete. A piezoelectric transducer is fixed into concrete and emits high-amplitude and short-duration pulses transformed into complex stress waves as they travel through concrete (pulse transmission). Eight Acoustic Emission (AE) sensors, attached on concrete surface, locate the pulse source spatially and chronically. It is shown that the transmitter localization progressively loses its accuracy with 3D spatial error up to 15% in the presence of crack 300 μm wide. The source localization error diminishes to 3.4% as the crack autonomously heals. The study aims at developing a monitoring system that accurately senses damage and can be applied on the next generation of smart engineering concrete in order to autonomously and repeatedly repair its cracks through piping network with supply of healing agent.